SHORT-TERM EFFICACY OF CONBERCEPT AND RANIBIZUMAB FOR POLYPOIDAL CHOROIDAL VASCULOPATHY. Issue 5 (May 2019) - Huang, Zhen; Ding, Qin; Yan, Min; Lian, Haiyan; Chen, Zhongshan; Chen, Xiao; Song, Yanping
Abstract : Purpose: To compare the 6-month efficacy of the intravitreal injection of conbercept or ranibizumab for patients with polypoidal choroidal vasculopathy (PCV). Methods: This is a retrospective case–control study involved 79 PCV eyes of 77 patients. The PCV eyes were treated with an intravitreal injection of either ranibizumab (n = 44) or conbercept (n = 35). Three monthly loading doses were injected and followed by retreatment as needed. The best-corrected visual acuity and angiographic characteristics were evaluated after 6 months. Results: The mean logarithm of the minimum angle of resolution best-corrected visual acuity had improved from 0.86 (Snellen equivalent, 20/145) at baseline to 0.70 (Snellen equivalent, 20/100) at 6 months in the conbercept group ( P < 0.001), and from 0.74 (Snellen equivalent, 20/110) at baseline to 0.63 (Snellen equivalent, 20/85) at 6 months in the ranibizumab group ( P = 0.032), respectively. The central foveal thickness was decreased from 407 ± 146 μ m to 230 ± 71 μ m in the conbercept group ( P < 0.001), and from 394 ± 93 μ m to 208 ± 56 μ m in the ranibizumab group ( P < 0.001). Polyps were completely regressed and in 21 (47.7%) eyes in the conbercept group at 6 months, significant higher than in 10 (28.6%) eyes in the ranibizumab group ( P = 0.029). Conclusion: Both conbercept and ranibizumab effectively increased the visual acuity and regressed the polyps of PCV eyes. No significant difference was found in the visual acuity improvement of the patients with PCV between the conbercept group and ranibizumab group at 6 months. However, conbercept was superior to ranibizumab monotherapy in the regression of polyps. Abstract : In this retrospective case–control study, the authors compared the 6-month efficacy of conbercept or ranibizumab for patients with polypoidal choroidal vasculopathy. The authors found that although both conbercept and ranibizumab were able to effectively increase patient's vision acuity; however, conbercept was superior to ranibizumab monotherapy in the regression of polyps.